The motives of the people of Bogor Regency to choose Golput in the 2014 legislative general election in the perspective of symbolic interactionism analysis - Mustaqim Mustaqim; Achmad Jamil (Jurnal Mantik, 2022)
Democracy of party in Indonesia five years have passed. Representatives of the people and the president - the vice president directly elected through the electoral process held by the General Election Commission (KPU). Many records were held by the Commission in general sorting this time, including decreasing the number 'white group' (abstentions/non voters) or numbers do not choose. One interesting phenomenon non voters presence in regions of the country is the phenomenon of non voters in Bogor, West Java. The focus of this research is to understand and explain the motive of the district community. Bogor in five districts choose non voters on the 2014 Pileg and explain the meaning of the legislative elections for non voters. By George Herbert Mead's symbolic interactionism be significant in this study, where views on individual behavior can be understood and explained through the frame of mind, self and society a vote. In addition, a review of literature on the concept of political communication is also a big impact as the scope research. Arguments regarding political participation as the substance of a democracy system also have the relevance in understanding the phenomenon of non voters. This research is within the constructivist paradigm, using descriptive qualitative approach and the case study method for the five districts (the district Cibinong, Citeurep, Bojong Gede, Gunung Puteri, and Cileungsi) as the representation of non voters to understand the motives and meaning of the legislative elections. This study had found that distrust of society becomes the motive non voters. Some distrust that consists of idealistic motives, experience motives, institutional motives, individualis motives and proximity motives.